Participatory training for digital empowerment: Developing graphic design skills with Canva - Parilah Parilah; Surya Adi Saputra; Wahyu Ari Wibowo; Siti Atwano Pisriwati; Deny Hadi Siswanto (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2025)
The advancement of digital technology requires rural communities to acquire relevant skills to adapt and enhance their competitiveness across various sectors. Responding to this need, this community service activity aimed to improve the digital skills of Gerbosari Village residents through graphic design training using the Canva application. The method employed was a participatory approach consisting of several stages, beginning with preliminary observation to identify participants’ needs, potentials, and supporting resources. The next stage involved preparing training materials and implementing sessions that included an introduction to graphic design and Canva, hands-on practice in creating accounts and exploring Canva features, as well as independent design exercises with team guidance. University students served as facilitators, helping participants overcome technical challenges to ensure an effective training process. The activity was held on July 7, 2025, at the Gerbosari Village Hall, Samigaluh District, Kulon Progo Regency, and was attended by 24 participants. The training materials focused on the basics of graphic design, the use of Canva, and practical exercises in designing logos and product packaging. Evaluation results indicated that 95% of participants were able to apply the acquired skills, demonstrating that this activity successfully enhanced digital competence, creativity, and self-confidence, while also supporting the community’s competitiveness in the digital era.   Abstrak Perkembangan teknologi digital menuntut masyarakat desa untuk memiliki keterampilan yang relevan agar mampu beradaptasi dan meningkatkan daya saing di berbagai bidang. Menyadari kebutuhan tersebut, kegiatan pengabdian ini bertujuan untuk meningkatkan keterampilan digital masyarakat Desa Gerbosari melalui pelatihan desain grafis berbasis aplikasi Canva. Metode yang digunakan adalah pendekatan partisipatif dengan beberapa tahapan, dimulai dari observasi awal untuk mengidentifikasi kebutuhan, potensi, serta sarana pendukung peserta. Tahapan berikutnya mencakup penyusunan materi, pelaksanaan pelatihan yang terdiri atas sosialisasi mengenai desain grafis dan Canva, praktik langsung membuat akun, pengenalan fitur-fitur Canva, serta latihan mendesain secara mandiri dengan pendampingan tim. Mahasiswa berperan sebagai fasilitator yang membantu peserta ketika menghadapi kendala teknis sehingga proses pelatihan berlangsung efektif. Kegiatan ini dilaksanakan pada 07 Juli 2025 di Balai Desa Gerbosari, Kecamatan Samigaluh, Kabupaten Kulon Progo dengan jumlah peserta 24 orang. Materi pelatihan difokuskan pada pengenalan dasar desain grafis, penggunaan Canva, serta praktik membuat desain logo dan kemasan produk. Hasil evaluasi menunjukkan bahwa 95% peserta mampu mengaplikasikan keterampilan baru, sehingga kegiatan ini terbukti meningkatkan keterampilan digital, kreativitas, dan kepercayaan diri masyarakat sekaligus mendukung daya saing di era digital. Kata Kunci: Canva; desain grafis; keterampilan digital